Comparative evaluation of centralized and decentralized solar street lighting systems - Joviancent, Kenzie; Halim, Levin; Naa, Christian Fredy (Institute of Advanced Engineering and Science, 2024)
Inadequate lighting can hinder outdoor activities such as traffic or pedestrian access. Solar street lighting system is planned to provide sufficient lighting for roads lacking proper illumination. DIALux software uses simulation to determine the lamp power and pole specifications, followed by applying formulas to establish component specifications. In this research, a performance comparison based on voltage drop and power losses will be conducted for solar street lighting systems with decentralized and centralized systems. With a road length of 130 meters and a width of 5 meters, simulations were performed for each variable of lamps (10, 12, 19, and 30 Watt). The calculations show that 4 streetlights are needed, and simulation results indicated that the most suitable lamp power is 12 Watt. The analysis showed that the centralized and decentralized designs do not have voltage drops exceeding the applicable limit. However, the centralized design has higher power losses amounting to 3.68 Watt. Another advantage of the decentralized design is its independence, with each load powered by a separate solar panel, while the centralized design is vulnerable to the overall system. In conclusion, the decentralized design is more suitable for implementation after comparing the centralized and decentralized designs based on the voltage drop and power losses.